Expression and secretion pattern of FljB of Salmonella enterica serovar Typhi in different culture conditions. (June 2016) - Zheng, Xueming; Zhang, Qisi; Ji, Ying; Zhao, Xin; Ni, Bin; Xu, Shungao; Huang, Xinxiang
Highlights: Flagellin of Salmonella is highly immunogenic and is a key protein recognized by the host immune system. SPI-1 inducing condition increases the secretion but not the expression level of FljB. SPI-2 inducing condition shut down the expression and consequential secretion of FljB. Salmonella may subvert the host's innate immune system through regulation of the expression and secretion of Flagellin.